Private Contracting, Law and Finance - Graeme Acheson; Gareth Campbell; John D. Turner (Queen's University Belfast, Queen's Management School, 2019)
In the late nineteenth century Britain had almost no mandatory shareholder protections, but had very developed financial markets. We argue that private contracting between shareholders and corporations meant that the absence of statutory protections was immaterial. Using circa 500 articles of association from before 1900, we code the protections offered to shareholders in these private contracts. We find that firms voluntarily offered shareholders many of the protections which were subsequently included in statutory corporate law. We also find that companies offering better protection to shareholders had less concentrated ownership.
Keywords: G32; G34; G38; K22; N23; N43; N83; 330; Law and finance; ADRI; shareholder protection; corporate ownership; common law